Unraveling the Underlying Arrhythmia Mechanism in Persistent Atrial Fibrillation: Results From the STARLIGHT Study. (June 2018) - Child, Nicholas; Clayton, Richard H.; Roney, Caroline R.; Laughner, Jacob I.; Shuros, Allan; Neuzil, Petr; Petru, Jan; Jackson, Tom; Porter, Bradley; Bostock, Julian; Niederer, Steven A.; Razavi, Reza S.; et al.
Abstract : Background: The mechanisms that initiate and sustain persistent atrial fibrillation are not well characterized. Ablation results remain significantly worse than in paroxysmal atrial fibrillation in which the mechanism is better understood and subsequent targeted therapy has been developed. The aim of this study was to characterize and quantify patterns of activation during atrial fibrillation using contact mapping. Methods: Patients with persistent atrial fibrillation (n=14; mean age, 61±8 years; ejection fraction, 59±10%) underwent simultaneous biatrial contact mapping with 64 electrode catheters. The atrial electrograms were transformed into phase, and subsequent spatiotemporal mapping was performed to identify phase singularities (PSs). Results: PSs were located in both atria, but we observed more PSs in the left atrium compared with the right atrium (779±302, 552±235; P =0.015). Although some PSs of duration sufficient to complete >1 rotation were detected, the maximum PS duration was only 1150 ms, and the vast majority (97%) of PSs persisted for too short a period to complete a full rotation. Although in selected patients there was evidence of PS local clustering, overall, PSs were distributed globally throughout both chambers with no clear anatomic predisposition. In a subset of patients (n=7), analysis was repeated using an alternative established atrial PS mapping technique, which confirmed our initial findings. Conclusions: No sustained rotors or localized drivers were detected, and instead, the mechanism of arrhythmia maintenance was consistent with the multiple wavelet hypothesis, with passive activation of short-lived rotational activity. Clinical Trial Registration: URL:https://www.clinicaltrials.gov . Unique identifier: NCT01765075. Abstract : Supplemental Digital Content is available in the text.